Environmental Factors Associated with Pulmonary Tuberculosis in Martapura’s Primary Health Center - Rosadi, Dian; Lasari, Hadrianti Haji Darise; Tazkiah, Misna; Fadillah, Ahmad; Sepira, Yuli; Maulidah, Siti (Universitas Diponegoro, 2025)
Pulmonary TB continues to be a health problem as it is the leading cause of death and ranks 10th in the world. The number of TB cases in South Kalimantan Province reached 5,636. Based on district/city, the highest number of TB cases was in Banjarmasin City with 868 cases, followed by Banjar Regency with 817 cases and Banjarbaru City with 483 cases, while the lowest number was in Balangan Regency with 187 cases. The purpose of this study was to analyse the relationship between ventilation, floor type and lighting with the incidence of pulmonary tuberculosis in the working area of Martapura 1 primary health center, Banjar Regency. This study was an observational analytical study with a case-control design approach. The study population consisted of 90 respondents, 30 people as cases and 60 people as controls. There was an association between ventilation (p-value = 0.03, OR 95% CI 4.5) and the incidence of pulmonary TB. Floor type (p-value = 0.211) and lighting (p-value = 0.577) were not associated with the incidence of pulmonary TB in Martapura 1 Health Centre.